Structural, Morphological, Optical Properties and Modelling of Ag Doped CuO/ZnO/AZO Solar Cell - Candan, Ilhan; Gezgin, Serap Yigit; Baturay, Silan; Kilic, Hamdi Sukur (Journal of Coating Science and Technology, 2022)
Copper (II) oxide (CuO) has attained significant attention from researchers because of its unique chemical and physical properties. Ag-doped CuO thin films have been produced on the soda glass substrate (SLG) by spin coating technique at different doping ratios. Structural, morphological, and optical properties of thin films produced depending on altered silver ratios have been examined through X-ray diffraction (XRD) spectroscopy, scanning electron microscopy (SEM), and UV-vis absorption spectroscopy, respectively. Band gaps of prepared undoped and 1% Ag-doped CuO thin films have been measured as 1.90eV and 1.63eV, respectively. Ag/undoped CuO and Ag-doped CuO/ZnO/AZO solar cells have been modelled, and their photovoltaic parameters have also been calculated using the SCAPS-1D simulation program. This work aims to investigate the photovoltaic parameters that would improve the efficiency of a solar cell. The effect of Ag atoms on the efficiency of CuO solar cells has been investigated depending on the acceptor density (Na), the interface defect density (Nt), and the operating temperature. Ag-doped CuO solar cells have shown the highest efficiency for Nt=1010 cm-3 and Na=6, 5x1016 cm-3 values. It has been well observed that as the operating temperature increases, the solar cells’ power conversion efficiency decreases. The highest charge generation rates in the undoped and Ag-doped solar cells have been determined as 1.49×1022 1/cm3.s and 1.51×1025 1/cm3.s, respectively. All the results, either theoretical or experimental, have been presented in this work and have been compared for a conclusion that has been made in detail.